Glycemic control was associated with nonprostate cancer and overall mortalities in diabetic patients with prostate cancer. Issue 3 (8th March 2022) - Lin, Chih-Chung; Wu, Ming-Fen; Chang, Yen-Lin; Sheu, Wayne Huey-Herng; Liou, Wen-Shyong
Abstract : Background: Diabetes mellitus (DM) can worsen the prognosis or survival in prostate cancer (PC) patients. We investigated whether glycemic control impacts mortality in PC patients with existing diabetes. Methods: All PC patients with or without preexisting DM were enrolled from 2006 to 2017. Mean hemoglobin A1c (HbA1c) values (<7%, 7%-9%, ≥9%) were used to represent glycemic control. Major outcomes included all-cause, PC-specific, and non-PC mortalities. Statistical analyses were performed using Cox regression models with adjusted mean HbA1c and other related confounders. Results: A total of 831 PC patients were enrolled (non-DM group, n = 690; DM group with a record of mean HbA1c values, n = 141). Results showed that the DM group with mean HbA1c level ≥ 9% (n = 14) had significantly increased risk for all-cause and non-PC mortality (hazard ratio [HR], 3.09; 95% CIs, 1.15-8.32; p =0.025 and HR, 5.49; 95% CIs, 1.66-18.16; p = 0.005, respectively), but not for PC-specific mortality (HR, 1.03; 95% CIs, 0.13-8.44; p = 0.975), compared with the non-DM group. Conclusion: Our findings indicate that PC patients with DM who had a mean HbA1c level ≥ 9% had higher risks of all-cause and non-PC mortality compared with non-DM subjects. Further large and long-term studies are needed to verify the effect of glycemic control in PC patients with DM.